Endocrown como alternativa de rehabilitación clínica en dientes tratados endodónticamente. Revisión bibliográfica - Sauca Gueledel, Yulady Dayanna (2023)
Endocrown is an alternative rehabilitation option for Endodontically Treated Posterior Teeth (ETPT) with extensive coronal destruction. It is a monoblock bonded to the walls of the pulp chamber chemically and mechanically. The following study is descriptive, analytical, and retrospective; for its elaboration, we searched for 45 bibliographic sources between retrospective and comparative clinical articles in the databases Pubmed, Scielo, Science Direct, and the Scientific Journal The Journal of prosthetic dentistry on topics related to Endocrown and its importance, the criteria evaluated to determine success and survival rate, in addition to the clinical characteristics of an ETT for Endocrown placement. So that considering the inclusion criteria, we took a sample of 18 clinical articles. After the analysis, we found that the importance of Endocrown lies in its conservative and esthetic approach, short working times, and the application of Endocrown in cases with root alterations. On the other hand, the criteria related to determining the success and survival rate, we found that the medium-term follow-ups present an adequate survival, the first molar, the digital technique, the ceramic reinforced with lithium disilicate, are ideal for achieving the objective, in addition, that it presents a positive clinical success based on the clinical criteria of the Public Health Service of the United States. And finally, an ETT must feature 5-10 degrees pulp chamber divergence toward occlusal, minimum tooth remnant height of 1-3 mm, limited or 2 mm interocclusal space, supragingival end line, and pulp chamber depth of 2-5 mm